Defiance in Evan Osnos' Novel Age of Ambition Chasing: Fortune, Truth, and Faith in the new China (2014) - Putri Rancak Karisga; Desvalini Anwar (English Language and Literature, 2019)
This article is about the analysis of novel Age of Ambition Chasing: Fortune, Truth and Faith in the New China (2014) by Evan Osnos that focuses on how the main character does the resistance toward the government. The problem in this analysis how far the main character in the novel exposes the issue about defiance. The aim of this analysis is to find out how far Evan Osnos’ novel Age of Ambition Chasing: Fortune, Truth, and Faith in the New China brings up and reveal the issue of defiance which is done by the main character in this novel. This analysis involved the fictional devices that are plot (conflict) and setting to support the issue of defiance. This analysis deals with the concept of power by Michel Foucault.